Interaction of Languages as the Main Factor of Linguistic Interference - Baghana, Jerome; N. Prokhorova, Olga; G. Voloshina, Tatiana; S. Blazhevich, Yuliya; L. Kuksova, Elena (International Journal of Engineering and Technology, 2018)
The article is devoted to the analysis of linguistic interference which can manifest itself at all language levels and in any part of the contacting systems which have structural differences. Researchers often subdivide this phenomenon in different types. It can be direct, inverse or bilateral. Depending on the type of speech activity one can distinguish impressive (receptive) or expressive (productive) interference. Depending on the form of manifestation interference can be explicit or implicit; intralingual (internal) or interlingual (external). The intensity of interference can vary and depends on subjective and objective factors. The study of this phenomenon cannot be limited to only one method and requires a complex approach.Â Â